Acetylcholinesterase inhibitory potential of plant-based phenolics in the treatment of Alzheimer’s disease: An in silico approach - Ashiru, Mojeed; Adigun, Rasheed Adewale; Babalola, Musa Oladayo; Ogunyemi, Sherif Olabisi; Junaid, Idris Oladimeji; Bello-Hassan, Maryam Titilayo; Fategbe, Mojisola Adebimpe; Baker, Myah Grace; Alabi, Kazeem Adelani; Emmanuel, Prince Ozioma; Balogun, Mohammed O. (Brazilian Journal of Science, 2025)
Alzheimer’s disease is the most prevalent cause of dementia, accounting for more than seventy per cent of all the reported cases. Among the various treatment strategies, inhibiting the action of acetylcholinesterase that breaks down the neurotransmitter acetylcholine is the most common. In this report, thirty-eight phenolic compounds were retrieved from the PubChem database and screened in silico against acetylcholinesterase. Non-covalent molecular docking, molecular mechanics-generalized born surface area (MM-GBSA), and molecular dynamics (MD) were used to predict their binding mode, affinity, free energy, and the stability of the protein-ligand complex. These were followed by drug-likeness screening and a rigorous prediction of their absorption, distribution, metabolism, excretion, and toxicity (ADMET) parameters. Myricetin (-13.9 kcal/mol) was predicted to have the highest binding affinity among the phenolics, though lower than the bound donepezil (-16.3 kcal/mol). To increase the binding affinity of myricetin, it was modified via a Schiff base formation, which gave the hydrazine B-1 a binding affinity of -17.7 kcal/mol, higher than that of donepezil. The molecular dynamics simulation showed that the modified ligands have better stability than myricetin. The ADMET and drug-likeness studies showed that the top four phenolics and myricetin analogue derivatives could be further developed as potential drug candidates. Keywords: Acetylcholinesterase, ADMET Modeling, Alzheimer’s disease, Molecular Docking, Molecular Dynamics